Longitudinal measurement of physical activity following kidney transplantation. (17th March 2014) - Dontje, M. L.; de, M. H. G.; Krijnen, W. P.; Corpeleijn, E.; Kok, T.; Bakker, S. J. L.; Stolk, R. P.; van der, C. P.
Abstract The purpose of this longitudinal observational study was to (i) examine the change of daily physical activity in 28 adult kidney transplant recipients over the first 12 months following transplantation; and (ii) to examine the change in metabolic characteristics and renal function. Accelerometer‐based daily physical activity and metabolic‐ and clinical characteristics were measured at six wk (T1), three months (T2), six months (T3) and 12 months (T4) following transplantation. Linear mixed effect analyses showed an increase in steps/d (T1 = 6326 ± 2906; T4 = 7562 ± 3785; F = 3.52; p = 0.02), but one yr after transplantation only 25% achieved the recommended 10 000 steps/d. There was no significant increase in minutes per day spent on moderate‐to‐vigorous intensity physical activity (T1 = 80.4 ± 63.6; T4 = 93.2 ± 55.1; F = 1.71; p = 0.17). Body mass index increased over time (T1 = 25.4 ± 3.2; T4 = 27.2 ± 3.8; F = 12.62; p < 0.001), mainly due to an increase in fat percentage (T1 = 30.3 ± 8.0; T4 = 34.0 ± 7.9; F = 14.63; p < 0.001). There was no significant change in renal function (F = 0.17; p = 0.92). Although the recipients increased physical activity, the majority did not meet the recommended levels of physical activity after one yr. In addition to the weight gain, this may result in negative health consequences. Therefore, it is important to develop strategies to support kidney transplant recipients to comply with healthy lifestyle recommendations, including regular physical activity.